The Colour Avant-Garde: a Living Space and a Concept for Style Formation in the New Epoch - Zheleznyak, Olga (project baikal, 2019)
The Colour Avant-Garde is a paradigm of the profession and culture in Russia of the early 20th century, a symbol of a new world perception and a feature of style formation. It is considered a living space of the new reality with an active intrusion of colour into all spheres of life in the country. The “new painting” is interpreted as a quintessence of the colour avant-garde, which introduces the ideas of style formation of the emerging epoch. The reminiscences of the colour avant-garde in contemporary culture show the significance of the avant-garde ideals and the attempts to use it as a fashion brand and a selling idea.
Keywords: colour avant-garde; new painting; suprematism; style formation